ESTIMASI SERAPAN KARBON PADA SUBSTRAT DASAR BERDASARKAN TINGKAT KERAPATAN MANGROVE DI KAWASAN EKOWISATA LANTEBUNG KOTA MAKASSAR - Asbar Asbar; Muhammad Yunus (Fakultas Perikanan dan Ilmu Kelautan Universitas Muslim Indonesia Makassar, Sulawesi Selatan, 2022)
The purpose of this study was to determine the density level of the mangrove ecosystem and to determine the absorption capacity of CO2 gas per hectare on the basic mangrove substrate found in the Lantebung Ecotourism Area, Makassar City. This research was conducted in July-December 2021 in the Lantebung Ecotourism Area, Makassar City. This study uses the Field Observation method to observe, measure and collect data, including primary and secondary data. Analysis of mangrove ecosystem density data and analysis of carbon uptake of mangrove substrates using the help of statistical data processing programs. Based on the results of the study, it shows that density can affect the amount of biomass, carbon stock content and CO2 absorption which has a strong relationship. The density of mangroves in plots I, II, and III (land-sea) has a higher density; The higher the density, the greater the total carbon stock and the ability to absorb CO2 gas per hectare in a mangrove ecosystem; Carbon content, carbon stock, and CO2 absorption capacity in mangrove ecosystems are higher at the surface than at depth but fluctuate up and down at each depth level.